A study evaluating the social and cultural context of a counselling booklet containing infant feeding and caring messages - a component of a community-based health package in Umlazi, KwaZulu-Natal - Hoosain, Naeema Yusuf (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references (p. 51-57).